Traitor to the throne / 2 - Hamilton, Alwyn (Hamilton, Alwyn. Rebel of the sands novel., 2018)
"Desperate to uncover the Sultan's secrets by spying on his court, gunslinger Amani is taken captive by the forces of the Sultan, whose agenda seems less tyrannical than originally believed"--Provided by publisher.